Chromomagnetic dipole-operator corrections in B̄→X sγ at O(β0αs2) - Ferroglia, A; Haisch, U (2010)
We calculate the fermionic corrections to the photon-energy spectrum of B̄→Xsγ which arise from the self-interference of the chromomagnetic dipole operator Q8 at next-to-next-to-leading order by applying naive non-Abelianization. The resulting O(β0αs2) correction to the B̄→Xsγ branching ratio amounts to a relative shift of +0.12% (+0.27%) for a photon-energy cut of 1.6 GeV (1.0 GeV). We also comment on the potential size of resummation and nonperturbative effects related to Q8. © 2010 The American Physical Society.